Role of Catestatin in the Cardiovascular System and Metabolic Disorders - Zalewska, Ewa; Kmieć, Piotr; Sworczak, Krzysztof (Frontiers in Cardiovascular Medicine, 2022)
Catestatin is a multifunctional peptide that is involved in the regulation of the cardiovascular and immune systems as well as metabolic homeostatis. It mitigates detrimental, excessive activity of the sympathetic nervous system by inhibiting catecholamine secretion. Based on in vitro and in vivo studies, catestatin was shown to reduce adipose tissue, inhibit inflammatory response, prevent macrophage-driven atherosclerosis, and regulate cytokine production and release. Clinical studies indicate that catestatin may influence the processes leading to hypertension, affect the course of coronary artery diseases and heart failure. This review presents up-to-date research on catestatin with a particular emphasis on cardiovascular diseases based on a literature search.